High proton conductivity within the ‘Norby gap’ by stabilizing a perovskite with disordered intrinsic oxygen vacancies - Kei Saito; Masatomo Yashima (Nature Communications, 2023)
Abstract Proton conductors are attractive materials with a wide range of potential applications such as proton-conducting fuel cells (PCFCs). The conventional strategy to enhance the proton conductivity is acceptor doping into oxides without oxygen vacancies. However, the acceptor doping results in proton trapping near dopants, leading to the high apparent activation energy and low proton conductivity at intermediate and low temperatures. The hypothetical cubic perovskite BaScO2.5 may have intrinsic oxygen vacancies without the acceptor doping. Herein, we report that the cubic perovskite-type BaSc0.8Mo0.2O2.8 stabilized by Mo donor-doing into BaScO2.5 exhibits high proton conductivity within the ‘Norby gap’ (e.g., 0.01 S cm−1 at 320 °C) and high chemical stability under oxidizing, reducing and CO2 atmospheres. The high proton conductivity of BaSc0.8Mo0.2O2.8 at intermediate and low temperatures is attributable to high proton concentration, high proton mobility due to reduced proton trapping, and three-dimensional proton diffusion in the cubic perovskite stabilized by the Mo-doping into BaScO2.5. The donor doping into the perovskite with disordered intrinsic oxygen vacancies would be a viable strategy towards high proton conductivity at intermediate and low temperatures.